The evolution of community based conservation and implications for Danish development cooperation - Mikkel Funder; Marie Ladekjær Gravesen (Danish Institute for International Studies (DIIS), 2021)
Biodiversity conservation is critical to address the loss of species and ecosystems, and a key component in Nature-based Solutions to development and climate change challenges. Denmark's strategy for development cooperation aims to strengthen biodiversity conservation and emphasises the importance of inclusive approaches. This DIIS Working Paper provides an overview of the evolution of community-based biodiversity conservation approaches, discusses selected overall lessons, and provides recommendations for Denmark's development cooperation.
Keywords: 330; Natural resources and environment; Land rights and investments; Climate change and environment; Development policy; Development in practice